Cornect family members play some music and sing some songs - Thomas, Gerald (1973)
John Jim Cornect joue le violon, Clyde Cornect joue la guitare et Mabel Bungay chante. Ils jouent cinq morceaux de musique et puis Mabel chante « Just when I needed you ». Ils jouent quelques autres chansons et puis Mabel chante « All I have to offer you is me. Gerald Thomas chante « Rock Island Line » et une jeune fille chante « Jolies demoiselles ». -- John Jim Cornect plays violin, Clyde Cornect plays guitar and Mabel Bungay sings. They play five pieces of music and then Mabel t sings “Just when I needed you”. They play a few more songs. Mabel sings “All I have to offer you is me”. Gerald Thomas sings “Rock Island Line” and a little girl sings “Jolies Demoiselles”. Transcription du F1762/C2391/CD-F0980 -- Transcript of F1762/C2391/CD-F0980